Sustainable finance: Evolution or revolution in the banking sector - Sredojević Slađana (Association of Serbian Banks, 2021)
Sustainable Development nowadays became a dominant paradigm for both public and private sectors. Several Strategic Agendas such as European Green Deal, the 2030 Agenda for Sustainable Development and the SDGs, Climate Action and others, at their core values have a great set of actions ranging from reduction of the CO2 levels, through financing of particular projects, to the improvement of general welfare of the economies and societies. Due to the funding gap, there is a growing interest for private sector financing, particularly sustainable financing, and its role and contribution to the mentioned ultimate goals. The objective of the research is to analyze the factors and progress that have been made in setting up the framework in sustainable financing at the EU and international level. This paper will aim to identify the direction and the channels of its potential impact on the banking sector, as well as to describe ways in which this new culture is developing in the banking sector. The paper will particularly try to identify if the banking sector is proactive or reactive, by observing initiatives and projects at the international, European, and local level that have been developing for the last two decades, and based on that, to try to assess if a concept of sustainability and sustainable finance represent an evolution (upgrade of the existing culture and practice) or a revolution (new paradigm) in the banking sector.